2010
DOI: 10.2527/jas.2009-2134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying creep feeding duration on the proportion of pigs consuming creep feed and neonatal pig performance1

Abstract: In Exp. 1, 54 sows (PIC Line 1050) and their litters were used to determine the effects of creep feeding duration on the proportion of pigs consuming creep feed and preweaning performance. Two groups of sows were blocked according to parity and date of farrowing and allotted to 3 experimental treatments in a randomized complete block design. Creep feeding was initiated at d 7, 14, and 18 from birth for durations of 13, 6, and 2 d of creep feeding. A creep diet (3,495 kcal of ME/kg, 1.56% standardized ileal dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 30 publications
(56 reference statements)
3
41
0
2
Order By: Relevance
“…However, Sulabo et al (2010a) reported that about 75% of the total litter creep feed intake was consumed in the last 7 d before weaning. Sulabo et al (2010c) also reported that pigs given access to creep feeding for 2 d before weaning consumed the same or greater amounts of creep feed compared with litters that were creep fed for 7 to 11 d. These observations indicate that creep feed intake is more related to maturity of piglets rather than the duration of creep feeding. More importantly, 3 d of creep feeding was chosen because most pig producers in the United States that practice creep feeding provide supplemental feed for only 2 to 7 d before weaning; thus, any effect of flavor addition must be observed in a short feeding duration.…”
Section: Expmentioning
confidence: 80%
See 1 more Smart Citation
“…However, Sulabo et al (2010a) reported that about 75% of the total litter creep feed intake was consumed in the last 7 d before weaning. Sulabo et al (2010c) also reported that pigs given access to creep feeding for 2 d before weaning consumed the same or greater amounts of creep feed compared with litters that were creep fed for 7 to 11 d. These observations indicate that creep feed intake is more related to maturity of piglets rather than the duration of creep feeding. More importantly, 3 d of creep feeding was chosen because most pig producers in the United States that practice creep feeding provide supplemental feed for only 2 to 7 d before weaning; thus, any effect of flavor addition must be observed in a short feeding duration.…”
Section: Expmentioning
confidence: 80%
“…Creep feeding duration influenced the proportion of eaters in whole litters (Sulabo et al, 2010c). Litters provided with creep feed for 13 d produced approximately 14% more eaters than litters fed creep for 6 and 2 d (80, 70, and 71% eaters, respectively).…”
Section: Expmentioning
confidence: 99%
“…(Carney‐Hinkle et al., ; Mori et al., ; Torrallardona, Andrés‐Elias, López‐Soria, Badiola, & Cerdà‐Cuéllar, ). Some studies reported that eater “creep feed” piglets have lower performance during the lactation and weaning weight (Pluske et al., ; Sulabo et al., ). However, the amounts of sow feed or faecal material ingested by the piglets during the lactation period is difficult to estimate and quite variable between littermates and were not determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is a positive correlation between preweaning and postweaning food intake under commercial conditions (Berkeveld et al, 2007;Sulabo et al, 2010). Piglets classified as eaters preweaning, by use of chromic oxide as a visual faecal marker of creep feed intake, have their first solid food intake postweaning faster than piglets classified as noneaters, show higher food intakes postweaning and have higher body weights in the early postweaning period, and a higher absorption by the small intestine, which is negatively correlated with postweaning diarrhoea (Bruininx et al, 2002;Kuller et al, 2007a,b).…”
Section: The Importance Of An Early Food Intakementioning
confidence: 92%